THE ROLE OF TECTONIC-MAGMATIC (THERMAL) ACTIVIZATION IN URANIUM ORE FORMATION IN ROCKS OF THE BASEMENT OF THE UKRAINIAN SHIELD - KUZMIN, A.; ANISIMOV, V.; MAKIVCHUK, O.; KRYUCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
During realization of the geological-prognostical researches in SE "Kirovgeology" the mar of tectonic-thermal activization (TTA) of the basement of the Ukrainian Shield (USh) is made. A material is grouped in the time intervals corresponding to established for USh epoch of uranium introducing. The analysis of the received information has allowed to define the main territories TTA controlling by zones of diagonal deep faults, and has shown connection with stages TTA of accumulation of uranium in the top part of an earth's crust down to formation of deposits for the account mainly of deep sources of uranium.